Implications of combined endocrinopathy of diabetes mellitus and hypothyroidism on pregnancy - P., Amudha; A., Karthika Devi; B., Manochithra; J., Delphin Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Hypothyroidism and diabetes are the endocrine disorders commonly observed in pregnancy and each has been associated with adverse maternal and fetal outcomes. Our objective was to study the implications of combined endocrinopathy of hypothyroidism and DM on pregnancy and its outcome. Methods: This prospective cohort study included 150 pregnant women with singleton gestation and who were screened for and diagnosed with DM and /or hypothyroidism. They were then divided into 3 groups: 1) Diabetes (n=69) 2) Hypothyroidism (n = 53) 3) DM and hypothyroidism (n=28). Perinatal and neonatal characteristics were compared among the 3 groups and statistically analysed. Results: Women with both DM and hypothyroidism had higher rates of first trimester abortions, preeclampsia, polyhydramnios, placental abruption, preterm deliveries, caesarean sections, postpartum haemorrhage and intrauterine fetal deaths when compared to other groups. On the contrary, rates of labour induction, fetal macrosomia and LBW new-borns were not statistically significant among the groups. Conclusions: Women with both DM and hypothyroidism are at high risk of developing perinatal complications and need intense surveillance for the same during their pregnancy for better outcome. Pregnant women diagnosed with one of these endocrinopathies should be screened for the other.